GDNF Family Ligands: A Potential Future for Parkinson's Disease Therapy - L. Mickiewicz, Amanda; H. Kordower, Jeffrey (CNS & Neurological Disorders - Drug Targets, 2011)
Parkinson's disease (PD) is a progressive neurodegenerative disorder characterized by motor dysfunction that occurs secondary to loss of dopaminergic neurons in the nigrostriatal pathway. Current pharmacotherapies focus on the replacement of lost dopamine to alleviate disease symptoms. However, over time this method of therapy loses effectiveness due to the continued death of dopaminergic neurons. Alternative strategies for the treatment of PD are aimed at modifying the disease state through the preservation of remaining dopamine neurons or even the regeneration of dopamine innervation through the use of neurotrophic factors. Neurotrophic factors are specialized proteins that can promote neuronal development, maintain neuronal health and modulate neuronal function in the ventral midbrain, making them candidates for the treatment of PD. Preclinial studies indicate that members of the glial cell line-derived neurotrophic factor family of ligands are capable of preserving the degenerating dopamine neurons. These promising results moved neurotrophic factor therapy to clinical trials in PD patients. To date, neurotrophic factor therapy is proven to be safe and well-tolerated in humans, but conclusive evidence of efficacy in the clinic remains to be determined. This review will discuss the preclinical and clinical experiments of glial cell line-derived neurotrophic factor family ligands for the treatment of PD.
Keywords: Gene therapy